Case Report: Pemetrexed-induced pseudocellulitis: a rare adverse effect to be recognized for better management - Proux, Emma; Chen, Jeanne; Bonhomme, Caroline; Pottier, Pierre; Piroth, Marie (Frontiers in Oncology, 2025)
Pseudocellulitis, a non-infectious inflammatory reaction mimicking infectious cellulitis, is a rare and often underrecognized adverse reaction to pemetrexed, frequently diagnosed late and leading to inappropriate treatments, particularly unnecessary antibiotic use. Through the presentation of a new case and a literature review conducted using Scopus and PubMed, we aim to clarify its clinical presentation and management. We report a new case of pemetrexed-induced pseudocellulitis (PIP), initially misdiagnosed and treated unnecessarily with multiple antibiotics. Following the correct diagnosis, the patient was successfully treated with both oral and topical corticosteroids. Pemetrexed had to be discontinued. PIP clinically mimics cellulitis, presenting unilaterally or bilaterally, sometimes accompanied by fever and inflammatory syndrome. Its onset is variable, occurring either after the initial pemetrexed administration or following subsequent cycles, with no clear dose dependency. Skin biopsy is not essential for diagnosis. Management typically involves local and/or systemic corticosteroids. Discontinuation of pemetrexed should be evaluated on a case-by-case basis and is not always necessary. Improved recognition of this condition is essential to avoid unnecessary interventions, enhance patient care, and prevent long-term complications due to prolonged inflammation.